Improvement of Non-motor Symptoms and Quality of Life After Deep Brain Stimulation for Refractory Dystonia: A 1-Year Follow-Up - Listik, Clarice; Cury, Rubens Gisbert; Casagrande, Sara Carvalho Barbosa; Listik, Eduardo; Arnaut, Debora; Santiago, Natally; Da Silva, Valquiria Aparecida; Galhardoni, Ricardo; Machado, Júlia de Lima Arantes; Almeida, Jessica Campelo de; Barbosa, Egberto Reis; Teixeira, Manoel Jacobsen; et al. (Frontiers in Neurology, 2021)
Introduction: Deep brain stimulation (DBS) is a treatment option for refractory dystonia's motor symptoms, while its non-motor symptoms (NMS) have been less systematically assessed. We aimed to describe the effects of DBS on NMS in refractory generalized inherited/idiopathic dystonia prospectively. Methods: We evaluated patients before and one year after DBS surgery and applied the following scales: Burke-Fahn-Marsden Rating Scale (BFMRS), NMS Scale for Parkinson's Disease (NMSS-PD), Parkinson's Disease Questionnaire-8 (PDQ8) short-form Brief Pain Inventory (BPI), Neuropathic Pain Symptom Inventory (NPSI), and Short-form McGill pain questionnaire (MPQ). Results: Eleven patients (38.35 ± 11.30 years) underwent surgery, all with generalized dystonia. Motor BFMRS subscore was 64.36 ± 22.94 at baseline and 33.55 ± 17.44 one year after DBS surgery (47.9% improvement, p=0.003). NMSS-PD had a significant change 12 months after DBS, from 70.91 ± 59.07 to 37.18 ± 55.05 (47.5% improvement, p=0.013). NMS changes were mainly driven by changes in the gastrointestinal (p=0.041) and miscellaneous domains (p=0.012). Seven patients reported chronic pain before DBS and four after it. BPI’s severity and interference scores were 4.61 ± 2.84 and 4.12 ± 2.67, respectively before surgery, and 2.79 ± 2.31 (0.00–6.25) and 1.12 ± 1.32 (0.00–3.00) after, reflecting a significant improvement (p=0.043 and p=0.028, respectively). NPSI score was 15.29 ± 13.94 before, while it was reduced to 2.29 ± 2.98 afterward (p=0.028). MPQ's total score was 9.00 ± 3.32 before DBS, achieving 2.71 ± 2.93 after (p=0.028). Conclusions: DBS improves NMS in generalized inherited/idiopathic dystonia, including chronic pain.